TRENDS IN FOREST CONSERVATION RESEARCH IN ACEH PROVINCE, INDONESIA THROUGH 2023: A BIBLIOMETRIC ANALYSIS - Hayati, Durrah; Samsudin, Yusuf Bahtimi; Armanda, Fahmy; Zikria, Virda; Muslih, Ali M; Andini, Sarah; Rahman, Syed Ajijur (Association of Indonesian Forestry and Environment Researchers and Technicians, 2025)
Forestry research is crucial for forest conservation, sustainable resource utilization, informing policy, promoting development, and enhancing ecosystem understanding. This research is vital for creating policies that ensure forest conservation and support local livelihoods, especially as forests face depletion and degradation threats. Aceh, which contains the largest remaining forests in Sumatra, plays a crucial role in both local and global conservation. Therefore, understanding Aceh’s forest conservation research is the first step to improve conservation practices. This study employs a bibliometric analysis of forest conservation research in Aceh, using Bibliometrix and Biblioshiny to analyze trends. A total of 354 relevant articles were identified using the Scopus database. The analysis shows publication patterns, including document types, article sources, and research affiliations with Syiah Kuala University being the primary contributor. The study also examined the knowledge structure through keyword frequency, trends, and keyword co-occurrences. Results show peer-reviewed journal articles and conference papers as the main publication types, with an increase in publications after 2005, coinciding with Aceh’s post-war political stabilization. Keywords, i.e. ‘forestry’, ‘conservation’, ‘fisheries’, and ‘ecosystem’ were found important. Topic trends revealed interest in forest management, ecosystem services, and disaster-related terms at post-2004 tsunami. Co-occurrence network analysis identified six main keyword clusters, i.e. biodiversity, conservation, land use and land cover change, and sustainable development.